ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA USAHA INDUSTRI KECIL KERAJINAN DI KABUPATEN PURBALINGGA - Sri Lestari; Lilis Siti Badriah (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
The purpose of this research are to 1know bussines performance of small-scale handycraft industry in Purbalingga and assumed variables influencing the industry. Data used are contribution income (as bussines performance indicator), education level, age, sum of family dependency, entrepreneur attitude, bussines experience today, bussines experience in the same field (as entrepreneur characteristic indicators), sum of labour, skill, wage, labour turnover (as labour characteristic indicators), bussines location, sum of partnerships, sum of suppliers (as environmental characteristic indicators) are collected from 90 respondent samples. Some problems of this research are how the bussines performance of small-scale handycraft industry in Purbalingga and assumed variables influencing the industry and are variables those include in entrepreneur characteristic, labour characteristic and environmental characteristic which explained in 13 variables influence to bussines performance, as simultaniously and partially and which dominant variables influence to bussines performance of small-scale handycraft industry in Purbalingga. The research method used are multiple regression and elasticity analysis. The conclusions of this research are (1) all of independent variables, as simultaniously, have significant influence to bussines performance, (2) as partially, the variables those influence significantly are education level, entrepreneur attitude, wage, bussines location, (3) The dominant variables influence to bussines performance of small-scale handycraft industry in Purbalingga are wage.